2016
DOI: 10.1111/jvh.12581
|View full text |Cite
|
Sign up to set email alerts
|

Intensification with pegylated interferon during treatment with tenofovir in HIV–hepatitis B virus co‐infected patients

Abstract: In hepatitis B "e" antigen (HBeAg) positive patients with hepatitis B virus (HBV) mono-infection, intensification of nucleos(t)ide analogue treatment with pegylated interferon (PegIFN) could help induce higher HBeAg seroclearance rates. Our aim was to determine the long-term effect of adding PegIFN to tenofovir (TDF)-containing antiretroviral therapy on seroclearance in HBeAg-positive patients co-infected with the human immunodeficiency virus (HIV) and HBV. In this prospective matched cohort study, 46 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Some of the more recent therapeutic strategies evaluated during HBV mono-infection have included add-on with peg-IFN after exposure to NA [ 107 , 108 ] or interruption of anti-HBV therapy [ 109 ]. No beneficial effect of peg-IFN intensification after TDF initiation has been observed in HIV-HBV co-infected patients [ 110 ], while treatment interruptions are generally discouraged due to their associated risk of hepatic flares and increased morbidity [ 16 , 111 ]. Since residual ccc-HBV DNA and integrated HBV DNA remain present in the hepatocyte after loss of HBsAg, discontinuation of anti-HBV treatment, particularly under immune suppression, could reactivate HBV [ 112 ] and thus anti-HBV-containing ART might be required despite functional cure.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the more recent therapeutic strategies evaluated during HBV mono-infection have included add-on with peg-IFN after exposure to NA [ 107 , 108 ] or interruption of anti-HBV therapy [ 109 ]. No beneficial effect of peg-IFN intensification after TDF initiation has been observed in HIV-HBV co-infected patients [ 110 ], while treatment interruptions are generally discouraged due to their associated risk of hepatic flares and increased morbidity [ 16 , 111 ]. Since residual ccc-HBV DNA and integrated HBV DNA remain present in the hepatocyte after loss of HBsAg, discontinuation of anti-HBV treatment, particularly under immune suppression, could reactivate HBV [ 112 ] and thus anti-HBV-containing ART might be required despite functional cure.…”
Section: Discussionmentioning
confidence: 99%
“…Current therapeutic strategies have been engineered to affect both innate (toll‐like receptor agonists) and adaptive (checkpoint inhibitors) arms of the immune system, but again are mostly experimental . Considering that these approaches may require a highly orchestrated immune response, as is the case with interferon‐based therapies , their efficacy could be reduced in immunocompromised HIV‐HBV co‐infected patients .…”
Section: Discussionmentioning
confidence: 99%
“…Limited studies of interferon have been performed in HIV-HBV co-infected individuals since the widespread availability of HBV-active ART, but recent studies have shown that the addition of pegylated interferon to HBV-active ART in HBeAg positive co-infected individuals did not lead to increased rates of HBeAg or HBsAg clearance, despite faster declines of antigen levels during treatment [172, 173] .…”
Section: Treatmentmentioning
confidence: 99%